Sumberdaya Teripang (Holothuroidea) Di Kepulauan Sekotong, Nusa Tenggara Barat - Yusron, Eddy (Universitas Atma Jaya Yogyakarta, 2003)
Observation on sea cucumber diversity was carried out at coastal waters of Sudak and Nanggu Islands in the West Part of Sekotong Island, April and June 2002. Sampling was done by using a transect quadrant of 1 m x 1 m. This sampling and observation on its microhabitat were conducted by scuba diving. Analyses on the sea cucumber community structure were based on its frequency of occurance, diversity, and density. The results showed that at both locations 11 species of sea cucumber were found where Holothuria scabra, H.atra, H nobilis, and Bohadschia marmorata were predominant, common and more evenly distributed than the other species.